Vocational Education for Students with Disabilities: A Qualitative Study of Teacher Challenges and Expectations - Gunarhadi, Gunarhadi; Yuwono, Joko; Rejeki, Dewi Sri; Supratiwi, Mahardika; Cahyani, Leni Ambar; Ayaoo, Dhevendren (FKIP Universitas Lampung, 2025)
Vocational Education for Students with Disabilities: A Qualitative Study of Teacher Challenges and Expectations. Objectives: This research aimed to analyze the challenges and expectations in providing vocational education for students with disabilities in both special and inclusive vocational high schools in the Solo Raya region, Indonesia. It sought to understand the barriers faced by educators and explore their expectations for improvements in vocational training for students with disabilities. Methods: This qualitative research employed a phenomenological design, focusing on 20 vocational education teachers from both special and inclusive vocational high schools. Data was collected through Focus Group Discussions (FGD) with semi-structured, open-ended questions guided by a set of research-specific themes. The data analysis followed a phenomenological analytic framework. Findings: This study identified several key challenges faced by educators in delivering vocational education to students with disabilities, including the lack of a specialized curriculum, insufficient teacher training, inadequate resources and infrastructure, and limited support for job placement after training. Furthermore, teachers highlighted the need for professional development opportunities and improvement in schools' accessibility. Moreover, stronger partnerships between stakeholders were seen as crucial for enhancing vocational education for students with disabilities. These barriers hinder students’ opportunities to gain essential vocational skills and transition successfully into the workforce in the Solo Raya Region. Conclusion: Vocational education for students with disabilities faces significant challenges; however, there are clear expectations for improvements in teacher training, infrastructure, and collaboration among stakeholders. Addressing these issues will not only enhance vocational education for students with disabilities but also empower them to gain greater independence, improve their quality of life, and contribute more fully to society. This provides critical insights into the context of Solo Raya, highlighting the need for targeted interventions to address these gaps. Keywords: challenges, expectation, vocational education, students with disabilities.